Stereotyping of Muslims in Germany: How the Presumed Influence of Media Stereotypes on Others Influences Attitudes and Behavioral Intentions Toward Muslims. (June 2021) - Sommer, Katharina; Kühne, Rinaldo
The study investigates the influence of media stereotypes on the degree of presumed media influence on others and the resulting effects for people's own attitudes toward a minority. We examine how the presumption of negative effects of media stereotypes on others can lead to a correction of one's own attitude toward Muslims. In an online experiment, we test the relationship among media stereotyping, presumed media effects, and attitudinal and behavioral consequences. The results show that one's own attitude toward Muslims is corrected when people presume a negative influence of media stereotypes about Muslims on other people.